The Possible Dream - Henderson, James C.; San Juan Coll., Farmington, NM. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
The "Possible Dream Scholarship Program" was developed at San Juan College (SJC) in New Mexico to encourage students to complete high school and attend college. Every 8th grader in San Juan County, regardless of their academic performance, receives a scholarship certificate of $125 to attend San Juan College and an invitation to enroll in the Possible Dream program. Two weeks later, their parents receive a letter from the college president explaining the tuition pre-payment program. Parents are asked to make $10 monthly payments to their child's scholarship account with the guarantee that when the 8th grader graduates from high school, he/she will have two full years of SJC tuition paid in full regardless of tuition increases that occur in the interim. The $125 scholarship that starts each student's account is funded by the San Juan College Foundation and U.S. West Communications, and the college board has agreed to freeze tuition at the rate in place when students joined the program. Now in its third cycle, the Possible Dream program has over 300 8th, 9th, and 10th grade participants, more than 50% of whom are minority students. Copies of the scholarship certificate, letters of invitation to join the program, and a guide distributed to participants of high school courses that help prepare for college are attached. (AJL)
ERIC Note: Paper presented at the Annual Convention of the American Association of Community and Junior Colleges (69th, Washington, DC, March 29-April 1, 1989).
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Bound Students; Community Colleges; High School Students; Incentives; Junior High School Students; Minority Groups; Parent Participation; Scholarship Funds; Scholarships; Student Recruitment; Tuition; Two Year Colleges; San Juan College NM -- Tuition Prepayment Programs; Reports, Descriptive; Speeches/Meeting Papers